Diversity and habitat preferences of mangrove species in Demta Bay, Papua Province, Indonesia - JOHN D. KALOR; ELHAM SUMARGA; DEVI N. CHOESIN; TATI S. SYAMSUDIN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Kalor JD, Sumarga E, Choesin DN, Syamsudin TS. 2026. Diversity and habitat preferences of mangrove species in Demta Bay, Papua Province, Indonesia. Biodiversitas 27 (3): d270338. https://doi.org/10.13057/biodiv/d270338. Mangrove species diversity is shaped by complex interactions among environmental factors that influence species-specific habitat preferences. This study aims to assess mangrove species diversity and identify the key environmental factors affecting their habitat preferences in Demta Bay, Jayapura, Papua, Indonesia. Fieldwork was carried out from September 1 to 20, 2024, across 10 research stations covering a total area of 40,000 m². Data were collected using the line transect plot method. At each station, two transects (100 m × 20 m) were established perpendicular to the shoreline, with a spacing of 100 m apart. Along each transect, four plots measuring 10 m × 10 m were established two plots with two replications, resulting in a total of 20 transects and 80 plots. Soil sampling and analysis were performed both in situ and ex situ, with four replications per transect. Data analysis included the Shannon-Wiener, Simpson, Margalef, and Pielou indices, as well as the Important Value Index. Habitat relationships were examined using Principal Component Analysis and Pearson correlation. This study documented 14 mangrove species from 6 families in Demta Bay, indicating moderate diversity. The composition of mangrove vegetation was characterized by an average density of 146.3±14.84 individuals/station (800m2), a diversity index of 1.36±0.25, a dominance index of 0.32±0.07, a species richness of 1.13±0.43, and an evenness index of 0.74±0.10, suggesting stable ecological interactions and functional redundancy among species. Key habitat variables, soil bulk density (0.63±0.21 g cm⁻³), soil pH (6.80±0.32), soil salinity (24.79±2.98 PSU), soil temperature (29.21±1.54°C), and soil moisture (48.70±18.53%), were measured across sites. This study demonstrates that soil characteristics exert a significant influence on mangrove species diversity and endemism in Demta Bay, Jayapura. Elevated salinity was linked to reduced species richness and evenness. Rhizophora apiculata and Rhizophora mucronata were the most dominant and widely distributed species, thriving in saline, compacted soils alongside Bruguiera sexangula. In contrast, Excoecaria agallocha favored moist soils with moderate pH, while Ceriops decandra performed best under slightly alkaline conditions. Given the geomorphological and ecological heterogeneity that drives localized species zonation in Demta Bay, as well as its benefits to local coastal communities, conservation efforts should focus on habitat-specific planting.